(3ajUd GdJaQbI Hjf Cgd GdESdGe hGdRfObIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3GdaVd Hf CMeO Hf GdaVd Hf CMeO Hf eMeO Hf eMeO GdHUQi s)
(3ChdgG (B:s
(3GdQGMdI aeG HGdg dG jSJHYO ef GdCTYQi bhdg (B:( (3Cf GdcdGe UaI hGMOI bGFe HPGJ Gddg heY chfg hGMOkG (B) s
(3BNQgG (B:s
(3aef YQa ef ZjQg Cfg eUOb dQShd Gddg Udi Gddg Ydjg Ke caQg ajchf GdecaQ HdG Cfg ecPH QShd Gddg Udi Gddg Ydjg agPG ZdW efg ai MGd TNU hGMO hGdMeO ddg hMOg s
(3GdChQGb eVWQHI ai GdJLdjO hGdfSNI cGedIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1304s
Keywords: (3GdJUha hGdBOGH GdTQYjIs